On the solution of the coupled Schrodinger-KdV equation by the decomposition method - Kaya, D; El-Sayed, SM (Elsevier Science Bv, 2003)
In this Letter, we consider a coupled Schrodinger-Korteweg-de Vries equation (or Sch-KdV) equation with appropriate initial values using the Adomian's decomposition method (or ADM). In this method, the solution is calculated in the form of a convergent power series with easily computable components. The method does not need linearization, weak nonlinearity assumptions or perturbation theory. The convergence of the method as applied to Sch-KdV is illustrated numerically. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: adomian decomposition method; coupled Schrodinger-KdV equation; traveling wave solution; numerical solution